The clinical outcomes of induction chemotherapy followed by radiotherapy vs. chemoradiotherapy in locally advanced hypopharyngeal squamous cell carcinoma: A retrospective study - Ke Jiang; Meiyan Zhu; Shasha He; Chengtao Wang; Yan Wang; Yufeng Ren; Zijun Xiang; Yong Chen (Heliyon)
Background: Stage III and IVA–B hypopharyngeal carcinoma presents a substantial risk of recurrence and metastasis. The treatment strategy remains uncertain. The objective of this observational study was to compare the outcomes of induction chemotherapy followed by radiotherapy (ICRT) and induction chemotherapy followed by chemoradiotherapy (ICCRT) in the treatment of locally advanced hypopharyngeal squamous cell carcinoma. Methods: 58 patients with stage III and IVA–B hypopharyngeal squamous cell carcinoma treated with ICRT (n = 26) or ICCRT (n = 32) were enrolled in the study. Baseline variables and toxicity rates were compared by Chi-squared test. Survival curves were constructed by the Kaplan-Meier method and compared by log-rank test. Multivariate Cox proportional hazard analysis was performed to evaluate the potential survival effects. Results: There were no significant differences in gender, age, smoking, drinking, T category, N category, overall stage, induction chemotherapy schemes and cycles between the two groups. The median follow-up time was 36.3 months (range, 2.3–97.5 months). The 2-year recurrence-free survival (RFS), locoregional recurrence-free survival (LRFS), distant metastasis-free survival (DMFS), and the 1-year, 2-year overall survival (OS) expressed no significant differences between the two groups. Furthermore, induction chemotherapy regimen of TPF achieved better OS than TP or PF (hazard ratio [HR] 0.395, 95 % confidence interval [CI] 0.178–0.879; P = 0.023), OS of patients in N2-3 category was worse than N0-1 (HR 2.594, 95 % CI 1.230–5.471; P = 0.012). In addition, the grade 3–4 therapy-associated toxicities during radiotherapy were higher in the chemoradiotherapy group than in radiotherapy alone group (P = 0.020). Conclusion: Following induction chemotherapy in patients with stage III/IVA-B hypopharyngeal squamous cell carcinoma, the concurrent chemoradiotherapy regimen provided similar survival rates with radiotherapy alone. Meanwhile, the incidence of treatment-related side effects during radiotherapy after induction chemotherapy were lower than that during chemoradiotherapy.